COVID-19-related healthcare closures negatively affect patient health and postoperative recovery. Issue 6 (6th September 2020) - Kopka, Michaela; Fritz, Julie-Anne; Hiemstra, Laurie Anne; Kerslake, Sarah
Abstract : Objective: To determine how COVID-19-related healthcare closures affect the health, recovery and access to resources of preoperative and postoperative orthopaedic sport medicine patients. Methods: Patients whose orthopaedic restorative surgeries were postponed as well as those within 3 months postoperative completed electronic questionnaires assessing physical health, emotional health, virtual care and access to resources. The EuroQoL-five-dimensional-three level (EQ-5D-3L) was included as a quantitative and standardised measure of general health status. Data were descriptively analysed using means, SD and qualitative measures. Results: A total of 115 patients whose surgeries were postponed completed the survey. Notable findings included that 41.7% of patients reported an increase in their symptoms during the COVID-19-related closures, and 68.7% described a negative impact on their physical health. Furthermore, 62.6% of patients reported that the postponement of their surgery would negatively affect their ability to return to work. A substantial percentage of patients (71.3%) reported that postponement of their surgery had an overall negative impact on their physical and/or emotional health. The mean health state on the EQ-5D-3L visual analogue scale (VAS) scale was 69.9 (SD=18.7). A total of 198 patients within 3 months postoperative completed the survey. A majority of patients (69.7%) indicated that COVID-19-related healthcare closures had an overall negative affect on their recovery. One-third of patients (35.4%) stated that they experienced increased symptoms as a direct result of limited postoperative follow-up. Less than half (41.4%) of patients accessed virtual physiotherapy, and only 42.9% of those that did found it to be helpful in some way. Virtual orthopaedic follow-up was deemed helpful by 61.3% of patients but many commented that it did not replace inperson visits. The mean health state reported on the EQ-5D-3L VAS scale was 76.9 (SD=15.6). Conclusion: This study highlighted the significant impact of COVID-19-related healthcare closures on preoperative and postoperative orthopaedic sport medicine patients. It revealed that restorative procedures play an important role in maintaining physical and emotional health, as well as returning individuals to work and leisure activities. It also showed that virtual care did not adequately replace the hands-on assessments of allied care and orthopaedic specialists. Level of Evidence: V.